Modelling the potential impact of climate change on future spatial and temporal patterns of biological control agents: Peristenus digoneutis (Hymenoptera: Braconidae) as a case study. Issue 5 (3rd March 2016) - Olfert, O.; Haye, T.; Weiss, R.; Kriticos, D.; Kuhlmann, U.
Abstract: Mechanistic species niche models were used to map the seasonal spatio-temporal dynamics of biological control pressure. Future climate scenarios were applied to these models to identify potential future trends in the patterns of biological control pressure through space and time during an annual seasonal cycle. Peristenus digoneutis Loan (Hymenoptera: Braconidae) is a parasitoid of Lygus Hahn (Hemiptera: Miridae) species, important pests of glasshouse and field crops throughout Europe and North America. Consistent with theoretical expectations, the modelled potential range of P. digoneutis expanded polewards and contracted from its southern temperature range limits. However, its distribution did not change consistently across continents or countries. Locations near the outer limits of the current modelled distribution were more sensitive to changes in future climates than locations near the central core. Weekly climate suitability and stress maps were developed to provide insight into seasonal adjustments that accompany changes in the potential range of pest species and their natural enemies. Climate change may increase the number of Lygus generations in western Canada allowing P. digoneutis to establish in areas, where biological control attempts had failed in the past.